Untangling the socio-political knots: A systems view on Indonesia's inclusive energy transitions. (January 2023) - Sekaringtias, Annisa; Verrier, Brunilde; Cronin, Jennifer
Abstract: National energy transitions face complex socio-political challenges, ranging from inertia to exacerbated inequalities. There are limited studies investigating these dimensions, especially in developing economies. This paper presents Indonesia, a country with high fossil fuel dependency, as a valuable case study to investigate the societal interplay affecting transitions. Interviews and literature analyses were conducted to assess barriers and levers to success. The findings are further analysed with systems thinking (ST), highlighting dynamic patterns and interdependencies. It is found that conflicting interests, inconsistent regulation, and low capability at the implementation level are among the most persistent barriers creating disparities between intentions and reality. These leave some groups disproportionately disadvantaged; notably, regions with fossil fuel-dependent income, informal sectors, and indigenous and local communities. Recommendations include the creation of an independent agency for the energy transition, and empowering regional participation. Addressing inclusion is imperative for social justice as well as to ensure adoptability and acceptance from all.